Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Turnover Intention (Studi Kasus Pada Karyawan UD Putra TS Kabupaten Majalengka) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
This study aims to determine the effect of compensation and work environment on turnoverintention at UD Putra TS Majalengka. This research uses descriptive analysis and verificationmethods. The data collection technique used is by distributing questionnaires. The populationin this study was UD Putra TS Majalengka, with a sample of 100 respondents. The samplingtechnique used was total sampling. The measurement scale of this study uses the Likert scale.The data instrument testing was done by using validity and reliability tests, while the dataanalysis was the classical assumption test, multiple regression analysis, determinationcoefficient analysis, and hypothesis testing.The results of the research that have been conducted show that compensation is in goodcriteria, work environment is in good criteria, and turnover intention is in high criteria. Theresults of the study that partially compensation has a significant effect on turnover intention,then the work environment has a significant effect on turnover intention. The results of theresearch simultaneously state that compensation and work environment together have asignificant effect on turnover intentions.